The Effect Of Motivation On Employee Performance Through Work Discipline At The Babelan District Office, Bekasi Regency - Fairly Maulana Andhito Putra; Supardi, Supardi; Agus Dharmanto (SEAN Institute, 2025)
This research aims to analyze the influence of motivation on employee performance through work discipline at the Babelan District Office, Bekasi Regency. Employee performance is a crucial factor in the effectiveness of public services, which can be influenced by various factors, including work motivation and work discipline. This research uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to employees at the Babelan District Office. The research results show that work motivation has a positive and significant effect on employee performance. Apart from that, work discipline also acts as a mediating variable that strengthens the relationship between motivation and employee performance. With high work discipline, the impact of motivation on improving performance becomes more optimal. Therefore, improving work discipline and a fair and transparent reward system are very necessary to increase employee productivity.has a positive but not significant effect on tax aggressiveness.